2015
DOI: 10.1149/2.0061514jes
|View full text |Cite
|
Sign up to set email alerts
|

Review—Understanding and Mitigating Some of the Key Factors that Limit Non-Aqueous Lithium-Air Battery Performance

Abstract: In this article, we have reviewed our work on understanding and mitigating some of the key factors that limit non-aqueous Li-air battery performance. Advances in Li-air battery technology require fundamental understanding of the discharge and charge processes. We first summarize an investigation of Li-air batteries based on a well-defined cathode surfaces having size-selected silver clusters. This work provided key insight into the nucleation and growth mechanism of the discharge product and its relationship t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 71 publications
(127 reference statements)
0
14
0
Order By: Relevance
“…To improve the performance of portable electronic devices, a range of batteries have been developed . Recently, Reddy et al.…”
Section: Figurementioning
confidence: 99%
“…To improve the performance of portable electronic devices, a range of batteries have been developed . Recently, Reddy et al.…”
Section: Figurementioning
confidence: 99%
“…The overall reaction is shown in Eq. 3 and the theoretical voltage, E 0 , of the reaction is 3.1 V. 5 Anode : 2Li → 2Li + + 2e − [1] Cathode : 2Li [2] Overall : 2Li + O 2 → 2Li 2 O 2 [3] Same electrochemical reactions take place in Li-air batteries, 6,7 in which O 2 is breathed from the ambient air. Since CO 2 and H 2 O in air would react with active components in batteries and deteriorate the performance, most laboratory experiments were conducted under pure O 2 environment.…”
mentioning
confidence: 99%
“…[8][9][10][11] Researches that focus on electrolyte solvents, lithium salts, catalysts and operating conditions have been carried out to increase the energy density, improve the efficiency, and extend the cycle life of non-aqueous Li-O 2 batteries. 5 Many studies on electrolyte solvents and lithium salts indicated that more stable non-aqueous electrolyte solvents and lithium salts are needed to improve the performance of reversible Li-O 2 batteries. [12][13][14][15][16] Xu et al 12 investigated effects of different organic electrolytes, including ethylene carbonate (EC), propylene carbonate (PC), triglyme z E-mail: xianglinli@ku.edu (TEGDME), butyl diglyme (BDG), dimethyl sulfoxide (DMSO), triethyl phosphate (TEPa) and sebaconitrile, on the discharge performance and discharge products of Li-O 2 batteries.…”
mentioning
confidence: 99%
“…We will focus on the mechanistic studies, rather than engineering aspects such as cell configuration and cathode morphology design, of which progresses are well summarized in recent elaborate review papers. [16][17][18] Reaction chemistries for discharge…”
mentioning
confidence: 99%